LAMA2 Neuropathies: Human Findings and Pathomechanisms From Mouse Models - Previtali, Stefano Carlo; Zambon, Alberto Andrea (Frontiers in Molecular Neuroscience, 2020)
Merosin deficient Congenital Muscular Dystrophy (MDC1A), or LAMA2-related muscular dystrophy (LAMA2-RD), is a recessive disorder resulting from mutations in the LAMA2 gene, encoding for the alpha-2 chain of laminin-211. The disease is predominantly characterized by progressive muscular dystrophy affecting patient motor function and reducing life expectancy. However, LAMA2-RD also comprises a developmentally-associated dysmyelinating neuropathy that contributes to the disease progression, in addition to brain abnormalities; the latter often underappreciated. In this brief review, we present data supporting the impact of peripheral neuropathy in the LAMA2-RD phenotype, including both mouse models and human studies. We discuss the molecular mechanisms underlying nerve abnormalities and involved in the laminin-211 pathway, which affect axon sorting, ensheathing and myelination. We conclude with some final considerations of consequences on nerve regeneration and potential therapeutic strategies.